If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(2x-1)-4(5x-2)=19-2(x+2)
We simplify the equation to the form, which is simple to understand
5(2x-1)-4(5x-2)=19-2(x+2)
Reorder the terms in parentheses
+(+10x-5)-4*(5x-2)=19-2*(x+2)
Remove unnecessary parentheses
+10x-5-4+*(+5x-2+)=+19-2+*(+x+2+)
Reorder the terms in parentheses
+10x-5+(-20x+8)=19-2*(x+2)
Remove unnecessary parentheses
+10x-5-20x+8=+19-2+*(+x+2+)
Reorder the terms in parentheses
+10x-5-20x+8=19+(-2x-4)
Remove unnecessary parentheses
+10x-5-20x+8=+19-2x-4
We move all terms containing x to the left and all other terms to the right.
+10x-20x+2x=+19-4+5-8
We simplify left and right side of the equation.
-8x=+12
We divide both sides of the equation by -8 to get x.
x=-1.5
| 2x+5x+(-3x)+(-3)=9 | | 3(2x-2)-3(5-3x)=3 | | 10=4-2 | | 4x-2=5x+8 | | -4(x-3)=36 | | -2x+1/2=1/3 | | 12(x+1)=108 | | 2x+1=-1/2 | | 5X+42=8X+11 | | 3x+5-7+9x-(-4)= | | -3(x+4)=-30 | | 15x-273=5x-13 | | 3(x-5)=-21 | | 8m^2+2m-3=0 | | 5x+5=115-7x | | 192=8(6)h | | 100-12x=28 | | x+3=114 | | x/2+84=-36 | | 3(3x-4)=-6 | | 2/3x-6=4 | | 5x+61=8x-14 | | -4(3x+5)=5(-2x-3) | | x/-2-8=22 | | 6x^2-13x-11=0 | | -4-5x=21 | | (x+3)(x-4)=o | | 30x+50y=240 | | 29=b/4+15 | | 5b+1/2b+2b+1/3b | | (7/8)x+1=(5/8)x | | -17+t/5=3 |